Product Design Worksheets as Procedural Scaffolding in the ScaPro-PjBL Model for Strengthening Pre-Service Physics Teachers’ TPaCK toward SDG 4 - Gaguk Resbiantoro; Wasis; Wahono Widodo (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To evaluate the validity and practicality of worksheets as a form of procedural scaffolding within the ScaPro-PjBL model for training TPaCK. Method: The design of these worksheets followed Plomp's (2013) design research stages: preliminary research, development/prototyping, and assessment. Developed alongside the innovative Scaffolded Product in Project-Based Learning (ScaPro-PjBL) model, the worksheets underwent expert review for validity and were piloted with 21 students in a limited pilot and 98 students in a broad pilot from two East Java campuses in Indonesia. Validity scores, reliability statistics (ICC(3, k) and Cronbach's Alpha), and practicality results were collected throughout these stages. Results: The worksheets were found to be valid, with an average validity score of 8.65 (very valid), an ICC(3, k) of 0.819 (good reliability), and an α of 0.839 (good reliability). Practicality was also confirmed, with an average score of 3.26-3.50 (very practical) in extensive trials. High reliability in practicality assessment was recorded using both ICC(3,k) and Cronbach's Alpha. Novelty: The six worksheets in this study were specifically designed as scaffolding in project-based learning to support the development of the ScaPro-PjBL model. The specifications for worksheet development are detailed in this article. This study contributes to SDG 4 (Quality Education) by providing structured, student-centered learning resources that enhance project-based learning implementation, promote higher-order thinking, and support equitable, high-quality science education.